Endodontic treatment of teeth with a wide apical opening – a clinical case - V. A. Popov; E. S. Pestova; S. A. Anisimova (Эндодонтия Today)
INTRODUCTION. The prevalence of apical periodontitis among the adult population exceeds 60%. This disease also occurs in adolescents in permanent teeth, and it is often detected in a state where the growth zone has died, and it is not possible to treat with calcium hydroxide to achieve apexogenesis. Therefore, there is a need to find and apply the most optimal dental materials for the treatment of dental periodontitis in adolescents. AIM. Presentation of our own clinical case of endodontic treatment of a tooth with a wide apical opening. MATERIALS AND METHODS. The article presents the result of treatment of a 15-year-old girl with an established diagnosis according to ICD-10: tooth 2.6 – K04.5 Chronic apical periodontitis (chronic granulomatous periodontitis). The tactics of dental care were aimed at stimulating apexification with calcium hydroxide-based filling material Metapaste (Meta Biomed, South Korea). The functional parameters of the tooth have been restored. The stability of the obtained result was assessed 3 months after the treatment using CBCT of the causal tooth. CONCLUSIONS. The presented clinical case demonstrates the successful endodontic treatment of a tooth in a teenager, in which treatment tactics aimed at stimulating apexification were applied. Observation of the patient for 1.5 years confirmed the success of the therapy, which manifested itself in the formation of the dentinal bridge and the positive dynamics of the tooth condition. The use of the calcium hydroxide-based drug Metapaste (Meta Biomed, South Korea) played a key role in achieving a stable clinical result. This case highlights the importance of timely and adequate dental intervention to achieve optimal treatment outcomes. A pediatric dentist should have the skills to use modern methods of treating periodontitis of permanent teeth with a wide apical opening to choose the best approach to therapy.